2022
DOI: 10.1002/ecs2.4252
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity and functional identity alter ant occurrence and activity in experimental grasslands

Abstract: Increasing plant species richness has been shown to positively affect the diversity of a range of other organisms, both above-and belowground. Although ants have a multitude of interactions with other organisms through their role as predators and mutualists, ants are a taxon that has rarely been investigated in studies of biodiversity effects. Ants are known to respond to changes in microclimatic conditions such as temperature and humidity, and these microclimatic conditions are known to be affected by vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…While our findings focus mainly on temperature at 5 cm soil depth, we also analysed data collected at 15 cm (all plots) and 60 cm depth (available only in one of the four experimental blocks; Extended Data Figs. 1,7,8,9). Overall, we observed that the effects of plant diversity at deeper soil depths were consistent with the results at 5 cm soil depth, although the effects at 60 cm depth were attenuated (Extended Data Figs.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…While our findings focus mainly on temperature at 5 cm soil depth, we also analysed data collected at 15 cm (all plots) and 60 cm depth (available only in one of the four experimental blocks; Extended Data Figs. 1,7,8,9). Overall, we observed that the effects of plant diversity at deeper soil depths were consistent with the results at 5 cm soil depth, although the effects at 60 cm depth were attenuated (Extended Data Figs.…”
supporting
confidence: 85%
“…Global climate change has led to changes in soil temperatures and has caused greater variance through climate extremes 6 . Soil temperature affects many physical, chemical, and biological processes and reactions, including water and nutrient uptake 3 , microbial activities, root growth 7 , carbon dioxide flux 8 , ant activity 9 and plant pests development 10 , thereby affecting seed germination, plant growth and productivity 4 . Fluctuations in soil temperature, including sudden chilling, freezing, or warming, can have dramatic impacts on plants, microorganisms, and soil animals 11 .…”
mentioning
confidence: 99%
“…However, even after controlling for abundance, the higher number of species was maintained and the true bug communities in open canopy treatments were consistently more diverse. Such a pattern may be common for insects in habitats with more light and higher temperatures (Achury et al 2022 ; Lettenmaier et al 2022 ) and might be related to the metabolic ecology of ectotherms (Prather et al 2018 ), where greater quatities of direct radiation in gaps increase the abundance and population growth of insects due to higher temperatures. Concurently, an increased amount and diversity of food resources, available for herbivores (Richards and Windsor 2007 ), might enhance the higher diversity in gaps.…”
Section: Discussionmentioning
confidence: 99%
“…The higher composition of ants in the treatment plots suggests an intrinsic demand for the resources and biotope condition patterns required by the ant species. Plant species diversity influences ants establishment and foraging parameters (Achury et al 2022).…”
Section: Discussionmentioning
confidence: 99%